Motivasi Belajar Mahasiswa pada Mata Kuliah Evaluasi Proses dan Hasil Pembelajaran Biologi - Siska Nerita; Lufri Lufri; Ali Amran; Yuni Adha (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This research is based on the low learning outcomes of biology education students in biology learning process and outcome evaluation courses. On the other hand, the biology learning process and outcomes evaluation course is a course that equips prospective educators to determine the success of the learning process that their students go through. One of the factors that can influence student learning outcomes is students' motivation in understanding evaluation material and the biology learning process, especially in designing and processing learning outcome assessment instruments. The aim of this research is to describe student learning motivation in terms of designing and processing learning outcomes assessment instruments. This research uses a qualitative approach and is descriptive in nature. The subjects of this research were students of the 2021 department of biology education at University of PGRI West Sumatra. The instruments used in this research were a learning motivation questionnaire and interview guide. The research results show that the overall learning motivation of biology education study program students is 76.2%, with high criteria. The conclusion is that the learning motivation of biology education study program students in biology learning process and outcome evaluation courses is at high criteria.